BUSINESS INCUBATOR MANAGER ROLES: A SYSTEMATIC LITERATURE REVIEW FROM LITERATURE BETWEEN 2001 - 2024 - Syahputra, Wira; Agustina, Tri Siwi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
Business Incubator already evolved from only providing resources, to becomes an places to develop the entrepreneur. This change makes a lot of task that should business Incubator provide and make managers roles more important than before. Even though, many research about the success of incubator an startup, but the roles of manager still need to be explored more. This systematic review aims to investigates the roles and the responsibilities of the business Incubator managers, their impact for the startup and incubator itself, and how can the managers align it with the long-term incubator goals. A systematic review conducted using PRISMA framework, and reported with the guidance of PRISMA2020 Checklist. Search from the publication that Examined incubator business manager published from 2001 -2024, From 129 article that found from the 129-article identified, 35 used for the final review. This Research found that Manager has a key role in facilitating mentees/incubates to access resources and networks, mentoring, and managing the incubator operations. Suggest the managers to become proactive for the success of the mentee/incubates. The study concludes that the role of incubator managers is crucial to fostering the entrepreneur, key factor for the success of incubator, it recommends for them to enhancing managerial roles to adapt on the dynamic environments.